2018
DOI: 10.1093/jcag/gwy060
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Care Models: Optimizing Adult Ambulatory Care in Inflammatory Bowel Disease

Abstract: Background Inflammatory bowel disease (IBD), including Crohn’s disease and ulcerative colitis, is a chronic, complex and unpredictable disease affecting an increasing number of patients worldwide from a young age. Inflammatory bowel disease is associated with multiple comorbidities and complications, requiring ongoing preventative, acute and chronic care. The purpose of this article is to review the literature on outpatient care models used to treat adults with IBD and to gain insight on how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…This type of multidisciplinary care delivery is often restricted to large academic centres ( 24–26 ). An integrated model of care in IBD has the potential to improve the quality of care, patient satisfaction, and mental and physical health and to reduce health care costs ( 23 , 27 , 28 ). During the pandemic, multidisciplinary visits have often been continued virtually with the individual seen on same day by different members of the multidisciplinary team in order to make joint treatment decisions ( 29 , 30 ).…”
Section: Changes In Health Care Deliverymentioning
confidence: 99%
“…This type of multidisciplinary care delivery is often restricted to large academic centres ( 24–26 ). An integrated model of care in IBD has the potential to improve the quality of care, patient satisfaction, and mental and physical health and to reduce health care costs ( 23 , 27 , 28 ). During the pandemic, multidisciplinary visits have often been continued virtually with the individual seen on same day by different members of the multidisciplinary team in order to make joint treatment decisions ( 29 , 30 ).…”
Section: Changes In Health Care Deliverymentioning
confidence: 99%
“…What are the advantages of a multidisciplinary program where each professional contributes to the care of the patient or an interdisciplinary program where professionals also directly interact with shared decisions taking into account the numerous factors contributing to outcomes? Various approaches have been used to determine the best care models from both a healthcare provider and a patient perspective and they unanimously support a “multidisciplinary” process, which in reality often describes an integrated multidisciplinary or interdisciplinary approach to practice [ 32 , 33 , 34 , 35 ]; see [ 36 ] for an in-depth discussion of various multidisciplinary care models. In a study utilizing semistructured interviews with IBD specialists, the consensus was that the ideal model involved “sharing collective expertise in a formalized manner” with interactions between subspecialty providers (i.e., GI physician and psychologist) being of the highest importance [ 32 ].…”
Section: Justifying An Integrated Model For Delivering Carementioning
confidence: 99%
“…In the UK, healthcare providers and patients achieved near unanimous consensus that care should be provided by a multidisciplinary team which meets regularly to discuss appropriate patients [ 34 ]. Another recent systematic review also concluded that an integrated care model incorporating a healthcare team that included a psychologist was the optimum model and is shown to decrease hospital admissions, IBD surgeries, comorbidities, and both direct and indirect costs [ 35 ]. It is clear that a care model that falls along the care spectrum between integrated multidisciplinary (in which providers work side-by-side with real-time meaningful communication/collaboration) and interdisciplinary (in which providers routinely see patients together) is supported by both providers and patients.…”
Section: Justifying An Integrated Model For Delivering Carementioning
confidence: 99%
See 1 more Smart Citation
“…For those not admitted, it is possible that many could have avoided ED care if an alternate option was available. Provision of emergency care to persons with IBD who do not truly need to be seen in the ED is expensive ( 7 ) and may lead to excess or inappropriate testing or treatment ( 8 ). We have studied the use of ED in Manitoba by persons with IBD using administrative data, however administrative data often does not allow for a granular assessment of the details of the exact reason for the ED visit ( 1 , 7 ).…”
Section: Introductionmentioning
confidence: 99%